Reconstructio Externa Linguae Ghiliacorum - Janhunen, Juha (Studia Orientalia Electronica, 2016)
Following the line of research initiated by Robert Austerlitz, this paper takes up the question concerning the prehistory of the Ghilyak or Nivkh language. Since Ghilyak is a genetic isolate, or a small family of closely related idioms, information on the earlier stages of the language can be obtained only from two kinds of sources, internal and external. Firstly, Ghilyak exhibits a large number of systematic morphophonological alternations and derivational correlations, which offer good opportunities for the application of the method of internal reconstruction. At the same time, due to external contacts, Ghilyak shares a number of diachronic developments, grammatical features, and lexical elements with the neighbouring languages. This paper, then, discusses some of the information that the traces of external contacts can yield about the prehistory of the Ghilyak language. В продолжение исследований, начатых Робертом Аустерлитцем, в настоящей статье рассматривается вопрос о предыстории нивхского языка. Поскольку нивхский язык является генетически изолированным, или представляет собой небольшую семью близкородственных языков, информацию о более ранних стадиях его развития можно получить только из двух типов источников – внутренних и внешних. С одной стороны, для нивхского языка характерны морфофонологические чередования и деривационные корреляции, которые предоставляют возможности для применения метода внутренней реконструкции. С другой стороны, в результате внешних контактов нивхский язык разделяет ряд исторических процессов, грамматических черт и лексических элементов с соседними языками. В статье обобщена информация о том, каким образом эти явления отражают предысторию нивхского языка.